Do static sources outside a Schwarzschild black hole radiate? - Higuchi, Atsushi; Matsas, George E. A. [UNESP]; Sudarsky, Daniel (American Physical Society (APS), 1997)
We show that static sources coupled to a massless scalar field in Schwarzschild spacetime give rise to emission and absorption of zero-energy particles due to the presence of Hawking radiation. This is in complete analogy with the description of the bremsstrahlung by a uniformly accelerated charge from the coaccelerated observers' point of view. The response rate of the source is found to coincide with that in Minkowski spacetime as a function of its proper acceleration. It is interesting that this quantum result appears to reflect the classical equivalence principle.